PENGEMBANGAN MEDIA KOMIK PADA TEMA LINGKUNGAN SAHABAT KITA UNTUK SISWA KELAS V SD - Khairul Azemi; Hidayat Hidayat (Jurnal Inovasi Penelitian, 2023)
This development research aims to develop comic media on the theme of our friend's environment that is suitable for learning. This research is a type of research and development using a 4D model. In this study, researchers carried out a 4D development model only up to the development stage. The instrument used to collect data is a questionnaire or questionnaire. Questionnaires are used to obtain study data from material experts, media experts and practicality data from the product to be developed in the form of teacher responses to the practicality of Comic Learning Media on the Environmental Theme of our friends. From the validation carried out by the media expert review, the percentage was 94.6% and from the material review validation, the percentage was 84%. From this percentage, it can be said that the comic media on the theme of our friend's environment which was developed "Very Valid" is used in the learning process.